Strategies to Improve Intermodal Transportation Connectivity Services in North Maluku - Hakim, Raudha; Sabaruddin, Sabaruddin (PT FORMOSA CENDEKIA GLOBAL, 2024)
Sea transport is one of the modes of transport providing great benefits such as a wide range, tariffs that are affordable to the public, safe and comfortable. To support the integration of the implementation of intermodal transport, it is necessary to integrate the service network, and the transportation infrastructure network. The purpose of this study is to determine the level of intermodal transportation services at Kupal Port, Bacan Island, South Halmahera Regency and the analysis method used was the Importance Performance Analysis (IPA) method and the Customer Satisfaction Index (CSI). The results of the study obtained the average satisfaction index value of Kupal Feeder Port service users on 16 (sixteen) service factors or attributes of 78.97 percent in the satisfied criteria.